Cultural significance of medicinal plants in healing human ailments among Guji semi-pastoralist people, Suro Barguda District, Ethiopia - Mersha Ashagre Eshete; Ermias Lulekal Molla (BMC, 2021)
Abstract Background Traditional medicine has remained the most affordable and easily accessible source of treatment in the primary healthcare system among communities unable to get modern medication. Ethiopian indigenous people have a long history of traditional plant utilization for treating ailments. The objectives of this study were to identify, document, and analyze the cultural significances of medicinal plants and their associated indigenous knowledge among Guji Semi-Pastoralist People, in Suro Barguda District, West Guji Zone, southern Ethiopia. Methods Semi-structured interview, focus group discussions, participant observation, and walk-in-the-woods methods were used to gather medicinal plants data. The informant consensus factor (ICF) and fidelity level (FL) values were calculated using quantitative approaches to check the level of informants' agreement on plant use and the healing potential of medicinal plant species, respectively. Indigenous knowledge of the use of medicinal plants for medicinal purposes among different informant groups was compared using t tests with R software. Results A total of 98 medicinal plant species belonging to 87 genera and 48 families were reported to be used for treating human ailments such as gastrointestinal diseases, breathing system diseases, dermatological diseases, and febrile diseases. Family Fabaceae was represented by 10 species followed by Lamiaceae (7 species). Four of the medicinal plants (Bothriocline schimperi Oliver & Hiern ex Bentham, Erythrina brucei Schweinf. emend. Gillett, Lippia adoensis Hochst. ex Walp. var. adoensis, and Millettia ferruginea (Hochst.) Hochst. ex Baker) were found endemic to Ethiopia and shrubs were more dominant (36 species). Ninety-one medicinal plant species were used for remedy preparation as soon as they were collected in their fresh form; 35.6% herbal medicine preparation was through crushing the plant parts and homogenizing them with cold and clean water; 159 (70.4%) traditional medicinal preparations were reported to be taken in their drinking form (orally). Conclusion The study indicated that the district is rich in different species of medicinal plants used to treat human ailments and indigenous knowledge about using these resources. Species with the recorded highest consensus for curative purposes are useful sources for further phytochemical and pharmacological validation for better utilization. Declining wild medicinal flora of the area calls for conservation priority.